Freshwater Mussels (Unionidae) of The Hatchie River, a Tributary of the Mississippi River, in West Tennessee - Don Manning (Hello World!, 1989)
A brief survey of the Hatchie River, a West Tennessee stream draining directly into the Mississippi River, during the summers of 1980 through 1983 revealed 33 taxa of unionacean mussels and the Asian clam, Corbicula fluminea (Muller, 1774). Three of these species. Uniomerus declivis (Say, 1831), Obovaria jacksoniana (Frierson, 1912) and Villosa vibex (Conrad, 1834), have not been previously reported as occurring in the State of Tennessee. The mussel assemblage of the Hatchie River shows a definite southern or Gulf Coastal affinity.